Flow Process Development and Optimization of A Suzuki-Miyaura Cross Coupling Reaction using Response Surface Methodology - Girish Basavaraju; Ravishankar Rajanna (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
A custom-made tubular flow reactor was utilized to develop a mathematical model and optimize the Suzuki-Miyaura cross coupling reaction. In this study, the experimentation was designed and executed through the statistical design of experiments (DoE) approach via response surface methodology. The effect of molar ratios of phenylboronic acid (1) and 4-bromophenol (2), temperature, the catalyst tetrakis(triphenylphosphine)palladium, and equivalence of aqueous tripotassium phosphate was studied in detail. The flow reactor profile was in good agreement with batch conditions and significant improvements to the overall reaction time and selectivity towards desired [1-1-biphenyl]-4-ol (3) was achieved. The Suzuki coupling reaction in batch condition would take on an average of 4 to 6 hours to complete, which was effectively accomplished in 60 to 70 minutes in this tubular reactor setup and could be operated continuously. The reaction model is in good agreement with the reaction conditions. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).